ANALISIS WALK TEST PADA CAKUPAN AREA ACCESS POINT DI GEDUNG FTI UKSW - Sesilia Kirana Vaniamosa; Wiwin Sulistyo (Jurnal Pendidikan Teknologi Informasi (JUKANTI), 2023)
This research aims to obtain signal strength data or Received Signal Strength Indication (RSSI) and visualize the coverage area that can be emitted of each access point of the SWCU FTI building area, also to generate recommendation for the latest access point position. This is because the students inside the SWCU FTI building need an internet connection with an optimal signal range to access learning materials. Data collection was carried out using the WiFi Analyzer application for the Walk Test method and the Ekahau Heatmapper application for visualization. The result of measurements show that the 2nd floor has the highest average RSSI value of -47.4 dBm (very good signal strength category) and the 4th floor has the lowest average RSSI value of -63.5 dBm (good signal strength category). However, good signal strength cannot be a reference in Ekahau’s visualization because there are still red areas (bad category) in several rooms that experience obstacles or attenuation